2015
DOI: 10.1016/j.invent.2014.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Women's experiences of factors affecting treatment engagement and adherence in internet delivered Behavioural Activation for Postnatal Depression

Abstract: a b s t r a c tIntroduction: Women with postnatal depression (PND) face significant barriers to treatment that may be overcome by internet based delivery of treatment. Demand for a self-help internet postnatal treatment offered via a parenting site was high, but attrition rates were also high. Aims: To gain patient perspectives on engagement and barriers to the Netmums' "Helping with Depression" treatment. Method: Semi-structured interviews were conducted with 17 participants selected from the Netmums trial. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
69
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(78 citation statements)
references
References 25 publications
9
69
0
Order By: Relevance
“…Identifying desired treatment formats of web-based treatments which fit the specific needs of postpartum women with anxiety may improve treatment outcomes and adherence (O'Mahen et al, 2015). So far, one study has looked at preferences for internet treatments specific to women with postpartum depression after pregnancy complications (Maloni, Przeworski, & Damato, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Identifying desired treatment formats of web-based treatments which fit the specific needs of postpartum women with anxiety may improve treatment outcomes and adherence (O'Mahen et al, 2015). So far, one study has looked at preferences for internet treatments specific to women with postpartum depression after pregnancy complications (Maloni, Przeworski, & Damato, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, we have reported elsewhere that baseline social functioning was related to number of modules completed in this sample (O'Mahen et al 2013), and we found that number of modules completed was associated with sudden gains. This finding is further supported by a qualitative study of women who took part in a minimally supported online BA treatment for PPD; women who had poor practical social support and worse functioning reported that they struggled to engage with the treatment content (O'Mahen et al 2015).…”
Section: Discussionmentioning
confidence: 71%
“…44 In addition, perinatal women have indicated that anonymity and flexibility in the time to perform the assessment or to receive treatment are important factors influencing their decision to search for mental health assistance. 58,59 Despite the potential of ICT in PeD screening, this review evidenced that the integration of ICT in this field is still very rare. In addition, our study revealed some strengths (e.g., the consensus about the screening tool to be used) and weaknesses (e.g., inconsistency in the cutoffs used, infrequent use of apps for telemonitoring, exclusion of teenage mothers, and a major focus on the postpartum period) of the existent literature.…”
Section: Discussionmentioning
confidence: 97%
“…Making the technology customizable is another way of enhancing engagement, as reported by women. 38,58 Virtual and augmented reality might serve this purpose, 73,74 as both technologies make customization feasible. To date, however, the utility of virtual and augmented reality for mental health screening in perinatal women remains unexplored.…”
Section: Implications For Future Research and Clinical Practicementioning
confidence: 99%
See 1 more Smart Citation